Association of the systemic immune-inflammation index with anemia: a population-based study - Chen, Shuying; Xiao, Jigang; Cai, Wenyu; Lu, Xulin; Liu, Chenxi; Dong, Yan; Zheng, Yingchun; Song, Ge; Sun, Qi; Wang, Huijun; Xiao, Zhijian (Frontiers in Immunology, 2024)
Background: Inflammation has been reported to be related to anemia. As a novel inflammatory marker, Systemic immune-inflammation index (SII) has not been studied with Anemia. The aim of this study was to investigate the possible relationship between SII and anemia.Methods: This retrospective cross-sectional survey was conducted using data from the 2005-2018 National Health and Nutrition Examination Survey (NHANES) population. In total, 19851 American adults aged ≥18 years were included. SII was calculated as the platelet count×neutrophil count/lymphocyte count. Anemia was defined as hemoglobin (Hgb) levels of < 13 g/dL in males and < 12 g/dL in females. Logistic regression analyses, subgroup analyses and sensitivity analyses were performed to investigate the relationship between SII and anemia.Results: Our study included a total of 19851 patients, of which 1501 (7.6%) had anemia. After adjusting for all covariates, the multivariate logistic regression analysis showed that a higher SII (Intransform) level was associated with increased likelihood of anemia (OR=1.51, 95% CI: 1.36-1.68, P<0.001). The association between SII and anemia exhibited a nonlinear manner. The positive correlation between SII and anemia was related to the severity of anemia. Subgroup analysis showed that there was no significant dependence on age, family income, body mass index, hypertension, kidney disease and cancer except gender on this positive association. Furthermore, sensitivity analyses confirmed the robustness of our results. Conclusion: Our study demonstrated that SII was positively associated with anemia especially among female participants. And this positive correlation was related to the severity of anemia. Further large-scale prospective studies are still needed to analyze the role of SII in anemia.